Preiskave površine katod iz ionske črpalke - Mozetič, Miran (Kovine zlitine tehnologije, 1999)
Pumping of hydrogen in sputter ion pumps is mainly due to dissociate adsorption of molecules on pure titanium surface and diffusion of atoms in the bulk cathode plates. The area on the surface, which is exposed to extensive sputtering is always clean and represent a sink for hydrogen. The biggest area of cathode plates of classical ion pumps is subjected to weak ion bombardment and may be contaminated with a thin film of titanium compounds during improper use with the pump. The layer prevents dissociation of hydrogen molecules and diffusion of atoms in the bulk. The composition of the surface layer of titanium cathodes of a triode pump was determined. We found out that a layer of impurities with the thickness of about 0.5 ?$μ$?m composed mainly of titanium, carbon, nitrogen and oxygen was formed on the surface. Since the sputtering coefficient for titanium carbide, nitride and oxide is much smaller than for pure titanium, the layer of impurities cannot be removed with the standard regeneration procedure.
Keywords: titan; vakuumske črpalke; ionske črpalke; površine